Implementation approach rational emotive behavior therapy as efforts to improve student discipline at SMTI Bandar Lampung vocational school - Aprilia, Reni; Kamil, Badrul; Syahril, Sulthan; Busmayaril, Busmayaril; Erlina, Nova (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study aims to analyze the application of Rational Emotive Behavior Therapy (REBT) in improving student discipline at SMK SMTI Bandar Lampung. A descriptive qualitative approach was employed to gain an in-depth understanding of REBT implementation in the educational context. Research data were collected through in-depth interviews with guidance and counseling teachers, as well as three 10th-grade students who frequently committed disciplinary violations. Data collection methods included structured interviews, direct observations, and documentation. Data analysis was conducted descriptively and narratively with the aid of NVivo 12 software to facilitate data organization and the identification of key themes. The findings indicate that the application of REBT techniques through individual counseling effectively transformed students’ behavior towards greater discipline. Through systematic stages such as problem identification, goal clarification, and reinforcement of rational thinking, students exhibited significant changes in their attitudes and actions towards school rules. These findings contribute significantly to the development of more effective counseling methods for enhancing discipline in educational settings.